Adenocarcinoma of small bowel: why is it so rare - Medeiros, Aldo Cunha Medeiros; Lima Filho, Albert Dikson de (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2024)
Small bowel adenocarcinoma (SBA) is a rare gastrointestinal neoplasm and despite the small intestine's significant surface area, SBA accounts for less than 3% of such tumors. Early detection is challenging and the reason arises from its asymptomatic nature, often leading to late-stage discovery and poor prognosis. Treatment involves chemotherapy with a 5-fluorouracil combination, but the lack of effective chemotherapy contributes to a generally poor prognosis. SBAs are linked to genetic disorders and risk factors, including chronic inflammatory conditions. The unique characteristics of the small bowel, such as rapid cell renewal and an active immune system, contributes to the rarity of these tumors as well as the high intratumoral infiltration of immune cells is associated with a favorable prognosis. Microsatellite instability in SBA is associated with a high tumor mutational burden, affecting the prognosis and response to immunotherapy. The presence of PD-L1 and programmed cell death, along with tumor-infiltrating lymphocytes, plays a crucial role in the complex microenvironment of SBA and contributes to a more favorable prognosis, especially in the context of high MSI tumors. Stromal tumor infiltratinglymphocytes are identified as independent prognostic indicators andthe association between MSI status and a favorable prognosis, emphasizes theimportance of evaluating the immune status of tumors for treatment decisions. In conclusion, small bowel adenocacinoma is a rare disease, the organ has some caracteristics that contributes to the small incidence of SBA. Finally, the diagnosis, treatmentand survival are challenging.